IDENTIFIKASI JENIS BAHAYA DAN PARAMETER PENILAIAN BAHAYA PADA PEKERJAAN KONSTRUKSI - Seng Hansen (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
This study aims to identify hazards and hazard assessment parameters in construction works through scientometric and integrative literature review analysis towards relevant academic literature. Scientometric analysis was adopted using Open Knowledge Maps application and followed by a qualitative analysis that produced new perspectives regarding hazard potentials and hazard assessment parameters in construction works. This study has successfully identified 40 construction hazards which grouped into six types, i.e. physical hazards, biological hazards, chemical hazards, technological hazards, psychosocial hazards, and combination. Furthermore, this study has also identified four assessment parameters, namely severity, probability, frequency, and exposure. The contribution of this study lies in its in-depth understanding on the identification of construction hazards and hazard assessment parameters through a comprehensive literature review. The findings are useful for practitioners to advance their safety management quality, as well as for academics to conduct further research on construction hazards, assessment and mitigations.